2004
DOI: 10.1590/s0100-84042004000400012
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal and vertical tree community structure in a lowland atlantic rain forest, southeastern Brazil

Abstract: -(Horizontal and vertical tree community structure in a lowland Atlantic Rain Forest, Southeastern Brazil). The horizontal and vertical tree community structure in a lowland Atlantic Rain Forest was investigated through a phytosociological survey in two 0.99 ha plots in the Intervales State Park, São Paulo State. All trees ≥ 5 cm diameter at breast height were recorded. 3,078 individuals belonging to 172 species were identified and recorded. The Shannon diversity index was H' = 3.85 nat.ind.-1 . The Myrtaceae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
1
32

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 24 publications
6
35
1
32
Order By: Relevance
“…Th e number of rare species (i.e. singletons) per hectare represented 17% of the plot richness, a value quite similar to other HRFs (14 to 17%, Assis et al 2004;Negrelle 2006) and lower than that observed values for forests on non-sandy soils (> 23% - Melo 2000Guilherme et al 2004;Losos 2004). In addition, Fisher´s alpha were much smaller than in 10 other tropical forest plots (values from 23 to 181) evaluated by Condit et al (2004), except by the Mudumalai dry deciduous forest plot (5.9).…”
Section: Forest Diversity and Compositionsupporting
confidence: 64%
See 2 more Smart Citations
“…Th e number of rare species (i.e. singletons) per hectare represented 17% of the plot richness, a value quite similar to other HRFs (14 to 17%, Assis et al 2004;Negrelle 2006) and lower than that observed values for forests on non-sandy soils (> 23% - Melo 2000Guilherme et al 2004;Losos 2004). In addition, Fisher´s alpha were much smaller than in 10 other tropical forest plots (values from 23 to 181) evaluated by Condit et al (2004), except by the Mudumalai dry deciduous forest plot (5.9).…”
Section: Forest Diversity and Compositionsupporting
confidence: 64%
“…Exceptions are found where there is illegal palm-heart harvesting (César & Monteiro 1995;Guilherme et al 2004;Guedes et al 2006), an activity not seen inside the plot. Myrtaceae also deserves special mention because it harbored twice as many species as the second richest family of the plot.…”
Section: Forest Diversity and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nos estádios iniciais há maior densidade de árvores, o que pode ser modificado rapidamente nos primeiros anos de sucessão (Finegan 1996). Com o aumento da idade das florestas, a estratificação vertical torna-se mais evidente, aumentando a complexidade estrutural da comunidade (Tabarelli & Mantovani 1999a;Guilherme et al 2004;.…”
Section: Introductionunclassified
“…Essas famílias, comumente são reportadas como as mais ricas em fl oresta ombrófi la densa (Tabarelli & Mantovani 1999;Oliveira-Filho & Fontes 2000;Moreno et al 2003;Guilherme et al 2004;Th omas et al 2008;2009) onde Myrtaceae é comumente referida com destaque tanto em regiões Submontanas (Mori et al 1983;Martini et al 2007;Th omas et al 2008) como em altitudes elevadas (Meireles et al 2008;Th omas et al 2009). …”
Section: Resultsunclassified